Soundwalk path affecting soundscape assessment in urban parks - Sun, Chutian; Meng, Qi; Yang, Da; Wu, Yue (Frontiers in Psychology, 2023)
Introduction Previous soundscape studies focused on sound perception and acoustic comfort in sampled sites and ignored the characteristics of the experiential process along the paths. Therefore, the effects of soundwalk paths on soundscape assessment should be explored. Methods In this study, a typical urban park was selected as a case study. The differences, characteristics, and effects of soundwalk paths on the soundscapes were explored, based on a soundwalk survey and laboratory study. Results The results are as follows: first, in the soundwalk, different soundwalk paths in the urban park had significant effects on the perceived extent of individual sound and soundscape assessment. Second, the soundscape assessment was consistent with the peak-end rule. In the laboratory experiments, the peak assessment of soundscape appeared at the end location of the soundwalk paths, it was critical to the overall soundscape assessment. Furthermore, in the soundwalk, the overall perceived extent of individual sound was strongly affected by the perceived extent of dominant sounds at the end location of the soundwalk paths. Third, in the soundwalk, the sound loudness contrast path (noise-quiet/quiet-noise) and sound source contrast path (natural-artificial sound/artificial-natural sound) were compared. In the noise-quiet path, the assessment of acoustic comfort was higher than that in the quiet-noise path, and the assessment of subjective loudness was lower than that in the quiet-noise path (p < 0.01). The subjective loudness of the artificial-natural sound path was lower than that in the natural-artificial sound path (p < 0.05). Discussion Thus, the design of the soundwalk paths was expected to enhance visitors’ soundscape assessment of urban parks.